PENGABDIAN KEPADA MASYARAKAT MELALUI RRI SURABAYA, BERANDA ASTA CITA: SOSIALISASI KESELAMATAN DAN KEAMANAN SEBAGAI TOLAK UKUR KUALITAS DESTINASI PARIWISATA BAGI MASYARAKAT - Upik Dyah Eka Noviyanti; Ni Nyoman Purwani (Nusantara Hasana Journal, 2026)
The Community Service (PKM) program aims to increase public awareness and understanding regarding safety and security aspects in the tourism sector, particularly as the primary standard for the quality of tourism destinations. This community service program collaborates with RRI Surabaya, a public education media outlet with extensive experience as an information medium. The community service program utilizes interactive outreach methods through radio broadcasts, interactive discussions, and the delivery of materials on tourism safety principles, risk mitigation, and emergency preparedness. This program is expected to foster a culture of tourism awareness oriented toward safety, security, and quality service, supporting sustainable tourism development and increasing tourist confidence in destinations in East Java.